2017
DOI: 10.1039/c6ra28722k
|View full text |Cite
|
Sign up to set email alerts
|

Design structure for CePr mixed oxide catalysts in soot combustion

Abstract: Four CePr mixed oxides with different structures were designed and synthesized using a solid-phase grinding method: a uniform solid solution of Ce and Pr (CePr-NN), Pr 6 O 11 -coated CeO 2 (CePr-NO), CeO 2 -coated Pr 6 O 11 (CePr-ON), and particle packing of CeO 2 and Pr 6 O 11 (CePr-OO) were obtained, and characterized by XRD, H 2 -TPR, TEM and TG. The results show that CePr-NN exhibits the best low temperature catalytic activity among the CePr catalysts. CeO 2 is the major active phase on the surface of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…This induced a sufficient and continuous supply of oxygen from the air to the reactant, which is crucial for catalytic activity. Furthermore, in contrast to the CeO 2 ‐NF sample, all the reduction peaks in the Ce X Pr 1−X O 2 ‐NF catalysts were within the range of the soot oxidation temperature (350–500 °C), which provides more available oxygen and thereby leads to a higher oxidation rate ,, . The TPR results confirmed that the incorporation of Pr into the ceria lattice (Ce X Pr 1−X O 2 ‐NF) improved the reducibility by oxygen and oxygen utilization in the samples.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…This induced a sufficient and continuous supply of oxygen from the air to the reactant, which is crucial for catalytic activity. Furthermore, in contrast to the CeO 2 ‐NF sample, all the reduction peaks in the Ce X Pr 1−X O 2 ‐NF catalysts were within the range of the soot oxidation temperature (350–500 °C), which provides more available oxygen and thereby leads to a higher oxidation rate ,, . The TPR results confirmed that the incorporation of Pr into the ceria lattice (Ce X Pr 1−X O 2 ‐NF) improved the reducibility by oxygen and oxygen utilization in the samples.…”
Section: Resultsmentioning
confidence: 64%
“…The reduction of Ce X Pr 1−X O 2 ‐NF catalysts showed relatively large LT peaks and appeared at lower temperatures compared with the CeO 2 ‐NF sample. The increase in the LT peak area demonstrates improvement of the reducibility, which is useful for the oxidation reaction ,. In the soot oxidation reaction, reducibility at 300–500 °C is a significant factor, representing a well‐timed oxygen‐release capacity .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, coprecipitation (Katta et al, 2010;Kumar et al, 2012;Venkataswamy et al, 2014;Muroyama et al, 2015;Devaiah et al, 2016), hydrothermal (Nakagawa et al, 2015;Piumetti et al, 2015), sol-gel (Oliveira et al, 2012;Zhou et al, 2015;Alcalde-Santiago et al, 2019), microemulsion (Fan et al, 2017), and solid-phase grinding have been used to prepare CeO 2 -based oxides. However, the drying methods are scarcely discussed.…”
Section: Introductionmentioning
confidence: 99%